The effect of successful and unsuccessful smoking cessation on short-term anxiety, depression, and suicidality - Capron, Daniel W. (2013)
Research on the mental health effects of quitting smoking is limited. Smokers with mental illness appear to be at a higher risk of unsuccessful smoking cessation. Recent work suggests they are at elevated risk for post-cessation increases in anxiety, depression and suicidal ideation. The current study tested the effects of successful and unsuccessful smoking cessation on short-term psychopathology in 192 community participants. Smoking cessation outcomes were classified using expired carbon monoxide levels that were taken at quit week, 1 and 2 week follow-up and 1 month follow-up. We found no psychopathology increases in participants who successfully quit smoking. For individuals struggling to quit our results partially supported a recently proposed struggling quitters hypothesis. However, the vast majority of individuals posited to be vulnerable by the struggling quitters hypothesis did not experience clinically significant increases in psychopathology. These findings have implications for clinicians whose clients are interested in smoking cessation.